THE EFFECT OF FINANCIAL LITERACY, FINANCIAL INCLUSION, AND GENDER BEHAVIOR ON INVESTMENT DECISIONS WITH INVESTMENT EXPERIENCE AS A MODERATING - Iwan Sujarwo; Musdalifah Azis; Wirasmi Wardhani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study investigates the determinants of investment decisions among culinary Micro, Small, and Medium Enterprises (MSMEs) in Balikpapan, Indonesia. It addresses the critical need to understand why MSMEs, vital to economic resilience, often underutilize formal investment channels despite growing financial access. The research specifically examines the direct effects of financial literacy, financial inclusion, and gender behavior on investment decisions, and tests whether investment experience moderates these relationships. Employing a quantitative explanatory approach, data were collected via surveys from 130 MSME owners/managers and analyzed using PLS-SEM. The findings reveal that financial literacy and investment experience have a significant positive direct impact on investment decisions. Contrary to expectations, financial inclusion and gender behavior showed no significant direct effects. Furthermore, investment experience did not function as a significant moderating variable. The study concludes that for culinary MSMEs in this context, practical knowledge and direct experience are paramount drivers of investment decision quality, overshadowing the role of their access to finance or gender-based behavioral predispositions. These results emphasize the importance of designing MSME support programs that prioritize experiential financial education over generic access expansion. The research contributes to behavioral finance literature by providing a nuanced, context-specific model for MSME investment behavior.